Time series analysis of the impact of consumption and energy use on environmental degradation: evidence from Malaysia - V. Rasiah, R. Ratneswary; Abdul Hamid, Baharom; Ow, Wilson Chee Seong; Habibullah, Muzafar Shah (School of Social Sciences, Universiti Sains Malaysia, 2012)
This study uses time-series analysis to investigate the long-run relationships and short-run dynamic interactions between environmental degradation (proxied by CO2 emissions) and the independent variables of consumption (proxied by income level or Gross Domestic Product per capita) and energy consumption in Malaysia over the period 1971 to 2008. The study applies the multivariate cointegration methodology to establish the possible causal relations between these variables. The cointegration test and the vector error correction model demonstrate the evidence of a positive long-run relationship between consumption and environmental degradation while energy consumption is negatively related to environmental degradation. The long-term elasticity coefficients of the independent variables on environmental degradation display relationships that are theoretically grounded. Further innovations analysis using variance decompositions lends evidence of the dominant influence of consumption and energy consumption in forecasting environmental degradation variance. The study concludes with an examination of policy implications of the findings.